Point-of-care tests for infection control: should rapid testing be in the laboratory or at the front line? - Moore, C. (The Journal of hospital infection, 2013)
A point-of-care test (POCT) offers a rapid result to manage a patient immediately. The presumed simplicity of such tests belies observed variation between personnel in performing and interpreting results when not appropriately trained. The number of point-of-care devices being developed for the diagnosis of infectious diseases is increasing; by understanding the limitations associated with their use, such tests for infection control purposes may be possible. To review the expanding repertoire of POCTs for the diagnosis of infectious diseases and to assess their utility as tools to aid in the reduction of hospital-acquired infection and outbreak management. A systematic review using PubMed and Scopus of published literature on the subject of POCTs for the diagnosis of infectious diseases. Although the number of publications describing POCTs is increasing, there remains a paucity of literature describing their use in a clinical setting. Of the literature reviewed, POCTs for the diagnosis of respiratory syncytial virus and norovirus have the greatest utility in an infection control setting, although the data suggest that sensitivity and training issues might be a problem. The future generation of POCT devices is likely to be molecular-based, improving sensitivity but at a significant cost to the user. POCTs have a role in infection control but currently the lack of good, consistent clinical data surrounding their use outside of the laboratory is a limiting factor in their implementation.